Comprehensive Analysis of the Alternaria Mycobolome Using Mass Spectrometry Based Metabolomics. Issue 3 (9th January 2020) - Gotthardt, Marina; Kanawati, Basem; Schmidt, Frank; Asam, Stefan; Hammerl, Richard; Frank, Oliver; Hofmann, Thomas; Schmitt‐Kopplin, Philippe; Rychlik, Michael
Abstract : Scope: Alternaria fungi are widely distributed plant pathogens infecting grains and vegetables and causing major harvest losses in the field and during postharvest storage. Besides, consumers are endangered by the formation of toxic secondary metabolites. Some of these secondary metabolites are chemically characterized as mycotoxins, but the majority of the Alternaria mycobolome still remains unknown. Methods and results: Fourier‐transform ion cyclotron resonance mass spectrometry (FTICR‐MS) and LC‐MS/MS are combined for the non‐targeted and targeted analysis of the metabolome of three A. alternata isolates and one A. solani isolate. Due to the ultra‐high resolution of FTICR‐MS, unique molecular formulae are assigned to measured m/z signals. The molecular formulae are matched to entries of the databases Antibase and Kyoto Encyclopedia of Genes and Genomes. The non‐targeted analysis of the fungal extracts reveals variations in the secondary metabolite profile of A. alternata and A. solani . Differences in the biosynthesis of dibenzo‐α‐pyrones, perylene quinones, tentoxin, and tenuazonic acid of the A. alternata and A. solani isolates are determined applying targeted LC‐MS/MS. Conclusion: FTICR‐MS analyses reveal clear differences in the metabolic profile of the A. solani and the A. alternata isolates. Abstract : Fungi of the genus Alternaria are plant pathogens infecting agricultural foods. Alternaria isolates are cultivated in a chemically defined liquid medium and the extracts are analyzed by ultra‐high‐resolution mass spectrometry (FTICR‐MS) and LC‐MS/MS. The targeted and non‐targeted analysis of the fungal extracts uncovers differences in the mycotoxin and metabolic profile of the A. alternata and the A. solani isolates.